Anti-Cancer Stem Cell Properties of Square Planar Copper(II) Complexes with Vanillin Schiff Base Ligands - Yihan Wang; Kuldip Singh; Chunxin Lu; Kogularamanan Suntharalingam (Molecules)
Current breast cancer therapies are unable to positively impact the lives of a significant proportion of diagnosed patients (24% based on 10-year survival rate). Breast cancer relapse and metastasis, the leading cause of breast cancer-associated deaths, is linked to the existence of breast cancer stem cells (CSCs). Redox-modulating metal complexes have been used to perturb the redox balance in breast CSCs and effect cell death. Here, we sought to expand this promising class of anti-breast CSC agents. Specifically, we report the synthesis, and anti-breast CSC properties of a series of copper(II) complexes bearing regioisomeric vanillin Schiff base ligands (1–4). X-ray crystallography studies show that the copper(II) complexes 1–4 adopt square planar geometries with the copper(II) centre coordinated to two vanillin Schiff base ligands. The most effective copper(II) complex within the series 4 displays low micromolar potency towards breast CSCs, up to 4.6-fold higher than salinomycin and cisplatin. Mechanistic studies indicate that copper(II) complex 4 elevates reactive oxygen species levels in breast CSCs, leading to activation of the JNK/p38 pathway and caspase-dependent apoptosis. Overall, this work expands the library of anti-breast CSC copper(II) complexes and provides insight into their mode of action.